Online Instructional Design Approaches Utilizing a Tablet PC - Lowry, Pam (International Journal of Advanced Corporate Learning (iJAC), 2009)
Online students can experience what instructional strategies can be utilized using a Tablet PC in online courses. This paper summarizes how inking in Word, Powerpoint, and Windows Journal can be effective in an online course both asynchronously and synchronously. Approaches concerning assignments, discussion boards, presentations, note taking are discussed and how they can be more effective for faculty members and students using a Tablet PC. Students actually experience how a Tablet PC can be utilized in an asynchronous and synchronous environment. In summary, preliminary data will be discussed from the students and professorâ??s point of view and next steps. As content and assignments are being designed and developed for an online graduate course, it is important to keep in mind teaching styles, studentâ??s learning styles, and a faculty memberâ??s approach to promoting a Tablet PC in an online course. Even though graduate students were not required to have a Tablet PC, the course enabled them to understand how effective a Tablet PC could be in an online course whether it was delivered asynchronous or synchronously. Powerpoint presentations were created to delivery asynchronously and synchronously content to students by utilizing a Tablet PC to illustrate concepts within the presentation. Assignments were created such as evaluating e-learning products, creating a Blackboard unit, evaluating online courses, group instruction sessions, and weekly discussion boards. As these assignments were graded, comments were written on their Word and Powerpoint files using Tablet PC inking. As the Tablet PC initiative is less than one year old at Lawrence Technological University, preliminary data is being collected from faculty members and students. After this class is taught summer 2008, additional research on the efforts of course design and student learning will be explored. The Tablet PC has the potential for enhancing online course delivery.